Effect of Acid on the Formation and Properties of Silane Membrane - YIN Xiao-tong, LIU Chun-hua, HE Fa-qi, FENG Li-ming (Cailiao Baohu, 2021)
At present, the effect of various acids on the hydrolysis and film-formation properties of silane has been less studied.In this paper, the influence of hydrochloric acid and acetic acid on the hydrolysis and polymerization process of KH560 and KH792 single silane and silane after their combination was studied by conductivity measurement.Moreover, the organic silane film was prepared by impregnating Q235 low carbon steel sheet and glass slide in the silane solution mixed with different acids.The resistance of corrosiveness and hardness for the organic silane film were evaluated by pencil hardness and Tafel polarization curve test.Results showed that acetic acid and hydrochloric acid could promote the hydrolysis of silane KH792, delay the polymerization of silanol after hydrolysis, and improve the stability of KH792 collosol.Due to too many cross-linking points, esterification, amidation and self-condensation of polyacids coincided such as oxalic acid and phosphoric acid, KH792 collosol was rapidly gelled into polymer.In addition, hydrolysis and copolymerization of KH560 and KH792 under the catalysis of acetic acid and hydrochloric acid could shorten the curing time of the coating at room temperature, improve the crosslinking density, enhance the density of the coating and significantly improve the corrosion resistance and pencil hardness of the coating.The surface dry time decreased from 96 h to 4 h, and the hardness of the composite film reached 3H.Besides, the self-corrosion current density of films in 3.5% NaCl solution decreased from 2.364 8×10-5A/cm2 to 4.967 0×10-6A/cm2.